Justice and trustworthiness factors affecting customer loyalty with mediating role of satisfaction with complaint handling: Zalo OTT Vietnamese customer case - Nguyen Ngoc Quang; Dao Cam Thuy (Cogent Business & Management, 2023)
The main objective of this research is to expand the satisfaction with complaint handling theory to the OTT (Over The Top) application by examining the perceptions of justice and trustworthiness factors affecting customer loyalty mediating role of satisfaction complaint handling. A quantitative online survey was conducted based on a questionnaire of 520 Vietnamese users who have had complaints about Zalo OTT service in 2022. Confirmatory factor analysis was used to evaluate the reliability and validity of scales; then, structural equation modeling was used to assess the fitness of the research model, formulated hypotheses and the indirect relationships. Findings show that satisfaction with complaint handling is strongly influenced by consumer trustworthiness and three subfactors of justice; it also plays a mediating role in the impact of justice and trustworthiness factors on customer loyalty. However, customer trustworthiness has the strongest direct impact on customer loyalty. This research can be used as a model on which firms will base themselves to create customer loyalty by manipulating justice, trustworthiness and satisfaction with complaint-handling factors.
Keywords: 650; justice theory; loyalty; Satisfaction with complaint handling; trustworthiness